Earnings restatements, changes in CEO compensation, and firm performance - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2008)
Prior research finds that earnings restatements are linked to CEOs' excessive option-based compensation and equity holdings. In this paper, we investigate whether firms that experience earnings restatements recontract with their CEOs to reduce their option-based compensation and if so, whether this leads to improved firm performance. Based on 289 restatement firms over the period 1997–2001, we find that the proportion of CEOs' compensation in the form of options declines significantly in the two years following the restatement. Furthermore, we document that this reduction is accompanied by a decrease in the riskiness of investments, as reflected in lower stock return volatility and subsequent improvements in operating performance. Our results suggest that a decrease in option-based compensation reduces CEOs' incentives to take excessively risky investments, resulting in improved profitability. Overall, our findings provide insights into the design and efficacy of CEO compensation contracts.